Clinical, morphological and genetic characteristics of patients with concurrent presence of JAK2 V617F and BCR::ABL1 - Naumann, Nicole; Dangelo, Vito; Lübke, Johannes; Bresser, Jakob; Hagen, Volker; Dengler, Jolanta; Metzgeroth, Georgia; Kreil, Sebastian; Hockenberger, Tabea; Hofmann, Wolf-Karsten; Fabarius, Alice; Saußele, Susanne; et al. (Scientific reports, 2025)
Diagnosis and treatment of chronic myeloid neoplasms with two concurrently present driver mutations is challenging. We report on 10 JAK2 V617Fpos/BCR::ABL1pos patients in whom both mutations were identified simultaneously in 5/10 (50%) patients or in whom BCR::ABL1 appeared a median of 14 years after the primary diagnosis of JAK2 V617Fpos myeloproliferative neoplasia (MPN) in the remaining 5 patients. Granulocyte-macrophage colony-forming unit (CFU-GM) analysis demonstrated subsequent acquisition of BCR::ABL1 in a pre-existing JAK2 V617Fpos clone in 8/9 (89%) of evaluable patients. Despite the presence of JAK2 V617F in all patients, atypical BCR::ABL1 transcripts (e1a2/e19a2) in 3/9 (33%) patients and additional somatic mutations in 5/9 (56%) patients, molecular remission of BCR::ABL1 was achieved with different ABL1 TKIs (imatinib, n = 2, dasatinib, n = 2, nilotinib, n = 3) in 7/9 (78%) patients. During a total of 217 months of treatment, concomitant treatment with ABL1 TKIs and ruxolitinib did not affect dosing, efficacy or side effects. We conclude that (i) a second driver mutation might occur in chronic phase MPNs, (ii) clonality analyses largely support a common disease origin, and (iii) the dose, efficacy and safety of ABL1 inhibitors and ruxolitinib are not mutually affected by concurrent treatment.
Gesehen am 16.09.2025
Im Titel ist "BCR::ABL1" mit einem Bereichsauflösungsoperator geschrieben